PROBLEM-BASED LEARNING WITH SCAFFOLDING TO IMPROVE NUMERACY LITERACY OF JUNIOR HIGH SCHOOL STUDENTS: PROBLEM-BASED LEARNING DENGAN SCAFFOLDING UNTUK MENINGKATKAN LITERASI NUMERASI SISWA SMP - Fathurrohman, Fani Laffanillah; Harry Dwi Putra, (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
Numeracy literacy is crucial because it can help someone understand the role or usefulness of mathematics in their daily lives. Therefore, it is necessary to research to improve students' numeracy literacy. The purpose of this research is to take action and analyze the use of the PBL model with scaffolding to improve students' numeracy literacy. Classroom action research with Kurt Lewwin model which consists of planning, implementation, observation, and reflection. Data collection techniques using tests and observation sheets. The data analysis technique used was qualitative and quantitative analysis. The subjects of this study were students of class VII-D at SMP Negeri 5 Cimahi. Data analysis can be concluded that Problem-Based Learning with Scaffolding can improve numeracy literacy, in cycle 1, we obtained an average value of 65 with a completeness rate of 50% which amounted to 20 students, and those who did not complete there were 20 students or 50%. While in cycle 2, the average score was 73.5 with a 70% completeness rate totaling 28 students and 12 students or 30% were not complete. With the application of the Problem-Based Learning model with Scaffolding, students are more active in participating in the learning process than before the action is given.